Women's Transformational Leadership and Teacher Loyalty at SDIT Cita Mulia Ajibarang - Rahmadini Mulya Aisah; Muh Hanif (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: This study examines how transformational leadership practiced by female leaders can enhance teacher performance and loyalty at the Integrated Islamic Elementary School (SDIT) Cita Mulia Ajibarang. This issue is important to explore because the increasing presence of women in strategic positions within Islamic educational institutions is not always accompanied by a comprehensive understanding of the effectiveness of their leadership styles. Teacher performance and loyalty in many schools are often hindered by weak communication, limited appreciation, and the lack of teacher involvement in decision-making. Therefore, a leadership style that is participatory, inspirational, and grounded in Islamic values is needed to create a harmonious work culture. Using a qualitative case study approach, data were collected through interviews, observations, and documentation. The study revealed three major findings: (1) the moral and spiritual exemplary behavior of female leaders fosters a collaborative culture and strengthens teacher trust; (2) empowerment through consultation and active participation enhances professional commitment; and (3) the integration of Islamic values such as amanah (trustworthiness), musyawarah (consultation), and rahmah (compassion) serves as an ethical foundation that nurtures teachers’ emotional loyalty toward the institution. Transformational leadership practiced by women not only improves the quality of teacher performance but also cultivates a humanistic and sustainable Islamic organizational culture. These findings contribute theoretically by expanding transformational leadership theory within the context of Islamic education and offer practical recommendations for madrasahs to adopt leadership models rooted in spirituality, exemplary conduct, and empowerment. Keywords: transformational leadership, women, teacher performance